(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The article analyzes informed consent focusing on the elements outlined by the European Regulation, considering the previous normative documents and the Italian legislation, as indispensable requirements and with reference to particularly vulnerable categories (incapable, minors, pregnant and breastfeeding women, patients in emergency conditions). The aim of the article is to identify, starting from the regulation but going beyond the regulation, elements of implementation of informed consent on the ethical level with particular reference to communication between researchers and participants, training of researchers, responsibility of both researchers and participants, and the role of ethics committees in the evaluation of informed consent.